Stereoselective Synthesis of the A,E-Ring Bicyclic Core of Calyciphylline B-Type Alkaloids - Kumar, Balagani Satish; Raghavan, Sadagopan (Synlett, 2019)
A stereoselective synthesis of the bicyclic unit constituting the A and E rings of calyciphylline B-type alkaloids is disclosed. The propionate ester of (1R)-cyclohex-2-en-1-ol, obtained by enzymatic resolution, is subjected to an Ireland–Claisen rearrangement. Subsequent reduction of the acid, Mitsunobu reaction to introduce a nitrogen functionality, oxidative cleavage to a dialdehyde, and intramolecular aldol and aza-Michael reactions afford the bicyclic subunit.
Keywords: asymmetric synthesis; alkaloids; chiral resolution; electrocyclic reaction; Michael addition; Mitsunobu reaction